'I'm not an activist!': digital self-advocacy in online patient communities. Issue 2 (15th March 2021) - Schermuly, Allegra Clare; Petersen, Alan; Anderson, Alison
ABSTRACT: For patient communities, digital media have dramatically transformed the options for action. This includes working collectively to change policies in ways that would have been difficult, if at all possible, before the internet. Yet, to date, the impacts of patients' growing use of digital media on their sense of collective agency have been little explored. Drawing on the findings from an Australian study on patients' use of digital media to access treatments (involving 50 interviews with participants from HIV/AIDS, breast cancer and neurodegenerative communities) and using a governmentality lens, this article sheds light on the changing character of patients' sense of agency in an age of digital media. We identify a shift in patients' conceptions of their agentic selves associated with the growing use of these media – from 'activists' to 'advocates' – and consider the implications for critical public health. As we argue, this 'digital self-advocacy' is manifest in patients' accounts of how they use digital media to achieve their goals and reflects the responsibilisation that is a hallmark of neoliberal governance. We suggest that digital self-advocacy offers a restricted vision of patient agency that limits rather than facilitates actions needed to respond to crises and to advance health justice. In our conclusion we consider whether the context and the nature of a condition or disease may also have a bearing on patients' sense of agency in an age of digital media, making reference to patient responses to a new illness phenomenon dubbed 'long COVID-19ʹ.